The sons - Kafka, Franza; Abdalrhman, Ahmed ([Cairo] master publishing, 2025)
I have only one request, " Kafka wrote to his the stoker, the 1913 publisher Kurt Wolff in Metamorphosis, and the judgment' belong together, both inwardly and outwardly. belong together, both inwardly and outwardly. thereis an obvious connection among the three, and, even more important, a secret one, for which reason i would be reluctant to forego the chance of having them published together in a book, which might be called the sons
Keywords: English fiction